2003
DOI: 10.1063/1.1569040
|View full text |Cite
|
Sign up to set email alerts
|

Improved performance of 325-nm emission AlGaN ultraviolet light-emitting diodes

Abstract: We report on AlGaN multiple-quantum-well light-emitting diodes over sapphire with peak emission at 325 nm. A pulsed-atomic-layer-epitaxy growth process was used to improve the material quality of the AlN buffer and the AlN/AlGaN strain-relief layers for reducing the nonradiative recombination. In addition, a modified device epilayer structure was used to improve the carrier confinement and the hole injection. A 40% improvement of external quantum efficiency is obtained, resulting in record high optical powers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 13 publications
0
47
0
Order By: Relevance
“…Group-III nitride semiconductors (AlGaN) can be developed for application in ultra-violet (UV) light emitters, UV photodetectors, white light emitters [1,2], and high-power electronics [3], because of its wide band gap distribution from 3.42 to 6.2 eV. The key issues for the growth of high-quality AlGaN epitaxial layers are crack formation and poor crystallization [4].…”
Section: Introductionmentioning
confidence: 99%
“…Group-III nitride semiconductors (AlGaN) can be developed for application in ultra-violet (UV) light emitters, UV photodetectors, white light emitters [1,2], and high-power electronics [3], because of its wide band gap distribution from 3.42 to 6.2 eV. The key issues for the growth of high-quality AlGaN epitaxial layers are crack formation and poor crystallization [4].…”
Section: Introductionmentioning
confidence: 99%
“…Chitnis et al [98] also demonstrated improved performance in DUV LEDs with AlN/AlGaN superlattice buffer layer. By using the pulsed atomic layer epitaxy (PALE) approach discussed in Section 6, and an AlN/Al 0.85 Ga 0.15 N superlattice strain-relief buffer, output power levels of 10.2 mW at 1 A pulsed current and 1 mW at 100 mA CW current were achieved in LEDs emitting at 325 nm and grown on sapphire substrates.…”
Section: Aln/algan Superlattice Buffermentioning
confidence: 96%
“…Gd 3C has a luminescent transition at a wavelength of 316 nm and therefore needs a very-large band-gap host material [34]. Presently, deep UV LEDs are mostly based on AlGaN [35][36][37], whereas for the green LEDs InGaN [38] or AlGaInP [39] are employed. The substitution of those materials by Si MOS structures would be highly desirable for low-cost and integrated applications.…”
Section: Rare-earth Doped Si-mos Light Emittersmentioning
confidence: 99%